Positive electrode active material, preparation method, lithium ion battery and electric equipment

By modifying the preparation method of lithium manganese iron phosphate composite material, the problems of high processing difficulty and poor electrochemical performance of lithium manganese iron phosphate material in lithium-ion batteries have been solved, achieving higher energy density and cycle stability, reducing manganese ion dissolution, and improving the overall performance of the battery.

CN119275285AInactive Publication Date: 2025-01-07ZHEJIANG LEAPENERGY TECH CO LTD

Patent Information

Application Number
CN202411798192.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Among existing lithium-ion batteries, lithium manganese iron phosphate materials have a large specific surface area, which makes them difficult to process and results in poor electrochemical performance. In addition, there is a problem of manganese ion dissolution, which affects the long-term stability and service life of the battery.

Method used

A modified lithium manganese iron phosphate composite material is used. This is achieved by mixing lithium manganese iron phosphate material with a smaller volume average particle size with lithium iron phosphate material with a larger volume average particle size, performing a first sintering, and then mixing it with a carbon source and a fluorine source for a second sintering to form a coating layer, which enhances the structural stability and conductivity.

Benefits of technology

It improves the processability of the positive electrode active material, increases energy density and cycle stability, reduces the dissolution of manganese ions, and enhances electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275285A_ABST
    Figure CN119275285A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium ion batteries, in particular to a positive electrode active material, a preparation method, a lithium ion battery and electric equipment. The positive electrode active material comprises a modified lithium iron manganese phosphate composite material, the modified lithium iron manganese phosphate composite material comprises a main body material, the main body material comprises a lithium iron phosphate material and a lithium iron manganese phosphate material, and the volume average particle size of the lithium iron phosphate material is greater than that of the lithium iron manganese phosphate material; and the lithium manganese iron phosphate material and the lithium iron phosphate material are partially fused, so that the lithium manganese iron phosphate material grows on the surface of the lithium iron phosphate material in situ. Therefore, the lithium ion battery prepared from the modified lithium manganese iron phosphate composite material not only has better electrochemical performance, but also can reduce the difficulty of production and processing of the lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to positive electrode active materials, preparation methods, lithium-ion batteries and electrical equipment. Background Art

[0002] In recent years, lithium-ion batteries have been widely used in wireless communications, transportation, aerospace, and other fields. Among them, lithium manganese iron phosphate (LMFP) has attracted widespread attention due to its low cost, high voltage platform, and energy density. Although the LMFP material itself has good electrochemical properties, its large specific surface area makes it difficult to process the LMFP material in the process of preparing lithium-ion batteries, and the electrochemical performance of the prepared lithium-ion batteries is poor. Summary of the invention

[0003] The main purpose of this application is to provide positive electrode active materials, preparation methods, lithium ion batteries and electrical equipment, aiming to solve the above-mentioned technical problems existing in the prior art.

[0004] In order to solve the above technical problems, the first technical solution adopted in the present application is: to provide a positive electrode active material, which includes a modified lithium iron manganese phosphate composite material, the modified lithium iron manganese phosphate composite material includes a main material, the main material includes a lithium iron phosphate material and a lithium iron manganese phosphate material, the volume average particle size of the lithium iron phosphate material is larger than the volume average particle size of the lithium iron manganese phosphate material, and the lithium iron manganese phosphate material is located on the surface of the lithium iron phosphate material.

[0005] In one embodiment, the volume average particle size of the lithium manganese iron phosphate material is 100 nm-500 nm.

[0006] In one embodiment, the volume average particle size of the lithium iron phosphate material is 0.8 μm-2 μm.

[0007] In one embodiment, the molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material is (1-10):1.

[0008] In one embodiment, the modified lithium manganese iron phosphate composite material includes a structural formula of LiMn x Fe 1-x PO4 material, wherein 0.1≤x≤0.6.

[0009] In one embodiment, the modified lithium manganese iron phosphate composite material further includes a coating layer, which is located on the surface of the lithium manganese iron phosphate material and the lithium iron phosphate material, and the coating layer includes C elements and F elements.

[0010] In one embodiment, the mass ratio of the coating layer to the modified lithium manganese iron phosphate composite material is (0.01-0.02):1.

[0011] In one embodiment, the coating layer has a thickness of 2 nm to 15 nm.

[0012] In one embodiment, the mass ratio of the C element to the F element is 1:(3-9).

[0013] The second aspect of the present application provides a method for preparing a positive electrode active material, comprising: mixing a lithium iron manganese phosphate material and a lithium iron phosphate material, and obtaining a main material through a first sintering, wherein the volume average particle size of the lithium iron phosphate material is larger than the volume average particle size of the lithium iron manganese phosphate material, and the positive electrode active material includes a modified lithium iron manganese phosphate composite material, and the modified lithium iron manganese phosphate composite material includes the main material.

[0014] In one embodiment, the molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material is (1-10):1.

[0015] In one embodiment, the first sintering step includes: in a nitrogen environment, pre-sintering the mixture of lithium iron manganese phosphate material and lithium iron phosphate material at 200℃-400℃ for 3h-5h, and then continuously raising the temperature to 500℃-600℃ for secondary sintering for 6h-10h.

[0016] In one embodiment, after the step of obtaining the main material, the method may further include: mixing the main material, a carbon source and a fluorine source, and performing a second sintering to obtain a modified lithium manganese iron phosphate composite material.

[0017] In one embodiment, the second sintering step includes: in a nitrogen environment, pre-sintering a mixture of the main material, the carbon source and the fluorine source at 300°C-450°C for 3h-5h, and then raising the temperature to 500°C-800°C for secondary sintering for 6h-10h.

[0018] In one embodiment, the mass ratio of the carbon source and the fluorine source to the host material is (0.1-0.25):1.

[0019] In one embodiment, the mass ratio of the carbon source to the fluorine source is 1:(3-9).

[0020] In one embodiment, the carbon source includes at least one of glucose and sucrose.

[0021] In one embodiment, the fluorine source includes at least one of ammonium fluoride, lithium fluoride, and iron fluoride.

[0022] A third aspect of the present application provides a lithium-ion battery, comprising the positive electrode active material of the first aspect and / or a method for preparing the positive electrode active material of the second aspect.

[0023] A fourth aspect of the present application provides an electrical device, comprising the lithium-ion battery of the third aspect.

[0024] In the technical solution of the present application, the lithium iron manganese phosphate composite material includes a main material, and the main material includes a lithium iron manganese phosphate material and a lithium iron phosphate material. The volume average particle size of the lithium iron manganese phosphate material is small, while the volume average particle size of the lithium iron phosphate material is large, so that the lithium iron manganese phosphate material can fill the gaps between the lithium iron phosphate material particles, thereby improving the processability of the slurry. The lithium iron manganese phosphate material has a small particle size and a high energy density. In addition, the lithium iron manganese phosphate material and the lithium iron phosphate material are partially fused, so that the lithium iron manganese phosphate material with a smaller particle size is in situ grown on the surface of the lithium iron phosphate material with a larger particle size, thereby retaining the morphology and structural framework of the lithium iron phosphate material and the lithium iron manganese phosphate material, enhancing the structural stability of the main material, and then improving the cycle stability of the modified lithium iron manganese phosphate composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 is a scanning electron microscope image of a lithium iron phosphate material according to an embodiment of the present application; Figure 2 is a scanning electron microscope image of a lithium manganese iron phosphate material according to an embodiment of the present application; Figure 3 is a scanning electron microscope image of a host material according to one embodiment of the present application; Figure 4 is a scanning electron microscope image of a modified lithium manganese iron phosphate composite material according to an embodiment of the present application; Figure 5 is a transmission electron microscope image of a modified lithium manganese iron phosphate composite material according to an embodiment of the present application; Figure 6 This is an elemental analysis image of a modified lithium manganese iron phosphate composite material according to an embodiment of the present application. DETAILED DESCRIPTION

[0026] Below, the battery cells, batteries and electrical equipment of the present application are described in detail with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0027] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0028] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0029] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0030] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may also include step (c), which means that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0031] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, "include" and "comprising" may represent that other components not listed may also be included or only listed components may be included or only listed components may be included.

[0032] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0033] Generally, lithium iron manganese phosphate material particles with smaller particle size are prepared to make lithium iron manganese phosphate have a larger specific surface area, which can make the surface of lithium iron manganese phosphate have more lithium insertion sites, thereby improving the energy density of lithium iron manganese phosphate. However, if the particle size of lithium iron manganese phosphate is too small, the viscosity of the slurry will be higher during the preparation of the slurry, which will be difficult to process and unevenly dispersed. In addition, it will be difficult to dry out the moisture after coating on the current collector, which will lead to poor electrochemical performance of the prepared lithium-ion battery. There is a lithium iron manganese phosphate material that is not compatible with a higher specific surface area and better electrochemical performance. In addition, due to the low lithium ion diffusion kinetics and complex phase transitions, the lithium iron manganese phosphate material itself has serious manganese ion dissolution problems, which affects the long-term stability and service life of the lithium-ion battery.

[0034] Based on the above problems, the first aspect of the present application provides a positive electrode active material, which includes a modified lithium iron manganese phosphate composite material, the modified lithium iron manganese phosphate composite material includes a main material, the main material includes a lithium iron phosphate material and a lithium iron manganese phosphate material, the volume average particle size of the lithium iron phosphate material is larger than the volume average particle size of the lithium iron manganese phosphate material, and the lithium iron manganese phosphate material is located on the surface of the lithium iron phosphate material.

[0035] In the technical solution of the present application, the modified lithium iron manganese phosphate composite material includes a main material, and the main material includes a lithium iron manganese phosphate material and a lithium iron phosphate material. The volume average particle size of the lithium iron manganese phosphate material is small, while the volume average particle size of the lithium iron phosphate material is large, so that the lithium iron manganese phosphate material can fill the gaps between the lithium iron phosphate material particles, thereby improving the processability of the positive electrode active material. The lithium iron manganese phosphate material has a small particle size and a high energy density. In addition, the lithium iron manganese phosphate material and the lithium iron phosphate material are partially fused, so that the lithium iron manganese phosphate material with a smaller particle size is in situ grown on the surface of the lithium iron phosphate material with a larger particle size, thereby retaining the morphology and structural framework of the lithium iron phosphate material and the lithium iron manganese phosphate material, enhancing the structural stability of the main material, and thereby improving the cycle stability of the modified lithium iron manganese phosphate composite material.

[0036] In one embodiment, the volume average particle size of the lithium manganese iron phosphate material is 100 nm-500 nm.

[0037] The volume average particle size of the lithium manganese iron phosphate material is relatively small, within the range of 100nm-500nm, so that the lithium manganese iron phosphate material has more lithium insertion sites, thereby increasing the gram capacity of the positive electrode active material.

[0038] The volume average particle size of the lithium manganese iron phosphate material may be 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, etc., or a range consisting of any two of the above values, for example, 100 nm-300 nm, 300 nm-500 nm, etc.

[0039] In one embodiment, the volume average particle size of the lithium manganese iron phosphate material is 100 nm-300 nm.

[0040] The volume average particle size of the lithium manganese iron phosphate material is within the above range, so that the lithium manganese iron phosphate material has more lithium insertion sites, thereby increasing the gram capacity of the positive electrode active material.

[0041] The volume average particle size of the lithium manganese iron phosphate material may be 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, etc., or a range consisting of any two of the above values, for example, 100 nm-200 nm, 200 nm-300 nm, etc.

[0042] In one embodiment, the volume average particle size of the lithium iron phosphate material is 0.8 μm-2 μm.

[0043] The volume average particle size of the lithium iron phosphate material is within the above range so that the positive electrode active material has a better gram capacity.

[0044] The volume average particle size of the lithium iron phosphate material may be 0.8 μm, 1.1 μm, 1.4 μm, 1.7 μm, 2 μm, etc., or a range consisting of any two of the above values, for example, 0.8 μm-1.4 μm, 1.4 μm-2 μm, etc.

[0045] In one embodiment, the volume average particle size of the lithium iron phosphate material is 0.8 μm-1 μm.

[0046] The volume average particle size of the lithium iron phosphate material is within the above range so that the positive electrode active material has a better gram capacity.

[0047] The volume average particle size of the lithium iron phosphate material may be 0.8 μm, 0.9 μm, 1.0 μm, etc., or a range consisting of any two of the above values, for example, 0.8 μm-0.9 μm, 0.9 μm-1 μm, etc.

[0048] In one embodiment, the molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material is (1-10):1.

[0049] When the molar ratio of the lithium iron manganese phosphate material to the lithium iron phosphate material is within the above range, the lithium iron manganese phosphate material can fill the gaps between the lithium iron phosphate material particles and make the content of the lithium iron manganese phosphate material in the positive electrode active material higher, thereby increasing the gram capacity of the positive electrode active material.

[0050] Among them, the molar ratio of lithium manganese iron phosphate material to lithium iron phosphate material can be 1:1, 3:1, 6:1, 8:1, 10:1, etc., or a range consisting of any two of the above values, for example, (1:1)-(3:1), (3:1)-(6:1), (6:1)-(10:1), etc.

[0051] In one embodiment, the molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material is (1-6):1.

[0052] In the embodiment of the present application, the molar ratio of the lithium iron manganese phosphate material to the lithium iron phosphate material is within the above range, so that the lithium iron manganese phosphate material can fill the gaps between the lithium iron phosphate material particles and make the content of the lithium iron manganese phosphate material higher, thereby increasing the gram capacity of the positive electrode active material.

[0053] The molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material may be 1:1, 2:1, 3:1, 4:1, 6:1, etc., or a range consisting of any two of the above values, for example, (1:1)-(3:1), (3:1)-(6:1), etc.

[0054] In one embodiment, the modified lithium manganese iron phosphate composite material includes a structural formula of LiMn x Fe 1-x PO4 material, wherein 0.1≤x≤0.6.

[0055] The modified lithium manganese iron phosphate composite material includes a structural formula of LiMn x Fe 1-x PO4 material, in which the molar amount of Mn element accounts for 0.1 to 0.6 of the total molar amount of Mn element and Fe element, so that the advantageous characteristics of the two elements of iron and manganese can be effectively combined, thereby making the positive electrode active material have better electrochemical properties.

[0056] In one embodiment, the modified lithium manganese iron phosphate composite material further includes a coating layer, which is located on the surface of the lithium manganese iron phosphate material and the lithium iron phosphate material, and the coating layer includes C elements and F elements.

[0057] The surface of the modified lithium manganese iron phosphate composite material has a coating layer, which includes C elements, which can improve the conductivity of the lithium manganese iron phosphate material and the lithium iron phosphate material. The coating layer also has F elements, which can form covalent bonds with the Mn elements in the lithium manganese iron phosphate material and the lithium iron phosphate material and the C elements in the coating layer, thereby strengthening the structural stability between the coating layer and the active material. In addition, the coating layer can also reduce the direct contact between the active material and the electrolyte, reduce the dissolution of manganese ions in the lithium manganese iron phosphate material, and thus improve the stability of the modified lithium manganese iron phosphate composite material.

[0058] In one embodiment, the mass ratio of the coating layer to the modified lithium manganese iron phosphate composite material is (0.01-0.02):1.

[0059] The mass ratio of the coating layer to the modified lithium manganese iron phosphate composite material is within the above range, so that the surface of the modified lithium manganese iron phosphate composite material is coated with the coating layer while the proportion of active material is high, thereby making the positive electrode active material have a higher gram capacity.

[0060] The mass ratio of the coating layer to the modified lithium manganese iron phosphate composite material can be 0.01:1, 0.015:1, 0.02:1, etc., or a range of any of the above values, for example, (0.01:1)-(0.015:1), (0.015:1)-(0.02:1), etc.

[0061] In one embodiment, the coating layer has a thickness of 2 nm to 15 nm.

[0062] The thickness of the coating layer is in the range of 2nm-15nm, which can not only improve the conductivity of the positive electrode active material, but also effectively reduce the dissolution of manganese ions in the lithium manganese iron phosphate material, thereby making the positive electrode active material have better stability.

[0063] The thickness of the coating layer may be 2 nm, 5 nm, 8 nm, 11 nm, 15 nm, etc., or a range of any of the above values, for example, 2 nm-8 nm, 8 nm-15 nm, etc.

[0064] In one embodiment, the coating layer has a thickness of 3 nm to 10 nm.

[0065] The thickness of the coating layer is in the range of 3nm-10nm, which can not only improve the conductivity of the positive electrode active material, but also effectively reduce the dissolution of manganese ions in the lithium manganese iron phosphate material, thereby making the positive electrode active material have better stability.

[0066] The thickness of the coating layer may be 3 nm, 5 nm, 6 nm, 8 nm, 10 nm, etc., or a range of any of the above values, for example, 3 nm-6 nm, 6 nm-10 nm, etc.

[0067] In one embodiment, the mass ratio of the C element to the F element is 1:(3-9).

[0068] The mass ratio of the C element to the F element in the coating layer is within the above range, which can effectively improve the cycle stability of the positive electrode active material.

[0069] The mass ratio of the C element to the F element in the coating layer may be 1:3, 1:5, 1:7, 1:9, etc., or a range consisting of any two of the above values, for example, (1:3)-(1:5), (1:5)-(1:9), etc.

[0070] The second aspect of the present application provides a method for preparing a positive electrode active material, comprising: mixing a lithium iron manganese phosphate material and a lithium iron phosphate material, and obtaining a main material through a first sintering, wherein the volume average particle size of the lithium iron phosphate material is larger than the volume average particle size of the lithium iron manganese phosphate material, and the positive electrode active material includes a modified lithium iron manganese phosphate composite material, and the modified lithium iron manganese phosphate composite material includes the main material.

[0071] In the technical solution of the embodiment of the present application, the lithium iron manganese phosphate material and the lithium iron phosphate material are mixed and then sintered for the first time to obtain the main material, which can retain the morphology and structural framework of the lithium iron manganese phosphate material and the lithium iron phosphate material at the same time, so that the lithium iron manganese phosphate material and the lithium iron phosphate material are partially fused. After the first sintering, the structure of the main material is regulated to reduce the internal defects of the material, thereby improving the cycle stability of the positive active material. The volume average particle size of the lithium iron manganese phosphate material is small, and the lithium iron manganese phosphate material is in-situ grown on the surface of the lithium iron phosphate material, so that the two materials are distributed more evenly, thereby making the gram capacity of the positive active material better.

[0072] In one embodiment, the preparation steps of the lithium iron manganese phosphate material include: dripping a lithium salt solution into a solution containing a manganese source, an iron source and a phosphorus source, controlling the pH of the solution within the range of 4.8-7.0, and after the reaction is completed, adding at least one of ethylene glycol, propylene glycol and glycerol to the mixed solution, and performing a hydrothermal reaction, and then washing and drying to obtain the lithium iron manganese phosphate material.

[0073] A mixed solution is obtained by dropping a lithium salt solution into a solution containing a manganese source, an iron source and a phosphorus source, and at least one of ethylene glycol, propylene glycol and glycerol is added to the mixed solution and then a hydrothermal reaction is performed, which is beneficial for controlling the morphology and particle size of lithium manganese iron phosphate.

[0074] In one embodiment, the preparation step of lithium iron phosphate includes: mixing a lithium source, an iron source, and a phosphorus source, dispersing the mixture in ethanol, and ball milling the mixture; and drying the mixture after ball milling to obtain a lithium iron phosphate material.

[0075] The particle size of lithium iron phosphate can be controlled by mixing a lithium source, an iron source, and a phosphorus source, dispersing the mixture in ethanol, and then ball milling the mixture.

[0076] Wherein, the lithium source may be at least one of lithium carbonate, lithium hydroxide, and lithium dihydrogen phosphate. The iron source may be at least one of ferric phosphate, ferrous sulfate, and ferric oxide. The manganese source may be at least one of manganese carbonate, manganese acetate, manganese phosphate, manganous phosphate, manganese dioxide, and manganese tetraoxide. The phosphorus source may be at least one of phosphoric acid, diammonium hydrogen phosphate, ammonium dihydrogen phosphate, and lithium dihydrogen phosphate. The lithium salt solution is a solution formed by using a lithium source as a solute.

[0077] In one embodiment, the molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material is (1-10):1.

[0078] When the molar ratio of the lithium iron manganese phosphate material to the lithium iron phosphate material is within the above range, the lithium iron manganese phosphate material can fill the gaps between the lithium iron phosphate material particles and make the content of the lithium iron manganese phosphate material higher, thereby increasing the gram capacity of the positive electrode active material.

[0079] Among them, the molar ratio of lithium manganese iron phosphate material to lithium iron phosphate material can be 1:1, 3:1, 6:1, 8:1, 10:1, etc., or a range consisting of any two of the above values, for example, (1:1)-(3:1), (3:1)-(6:1), (6:1)-(10:1), etc.

[0080] In one embodiment, the molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material is (1-6):1.

[0081] In the embodiment of the present application, the molar ratio of the lithium iron manganese phosphate material to the lithium iron phosphate material is within the above range, so that the lithium iron manganese phosphate material can fill the gaps between the lithium iron phosphate material particles and make the content of the lithium iron manganese phosphate material higher, thereby increasing the gram capacity of the positive electrode active material.

[0082] The molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material may be 1:1, 2:1, 3:1, 4:1, 6:1, etc., or a range consisting of any two of the above values, for example, (1:1)-(3:1), (3:1)-(6:1), etc.

[0083] In one embodiment, the first sintering step includes: in a nitrogen environment, pre-sintering the mixture of lithium iron manganese phosphate material and lithium iron phosphate material at 200℃-400℃ for 3h-5h, and then continuously raising the temperature to 500℃-600℃ for secondary sintering for 6h-10h.

[0084] The lithium iron manganese phosphate material and the lithium iron phosphate material are placed in a nitrogen environment, and pre-sintered at 200℃-400℃ for 3h-5h, and then secondary sintered at 500℃-600℃ for 6h-10h to obtain the main material. The lithium iron manganese phosphate material and the lithium iron phosphate material can be fused through the first sintering, so that the lithium iron manganese phosphate material grows in situ on the surface of the lithium iron phosphate material, while retaining the crystal structure of the two materials, making the two materials more evenly distributed, thereby improving the electrochemical performance of the positive electrode active material.

[0085] Wherein, in the first sintering step, the pre-sintering temperature may be 200°C, 250°C, 300°C, 350°C, 400°C, etc., or a range consisting of any two of the above values, for example, 200°C-300°C, 300°C-400°C, etc. The pre-sintering time may be 3h, 3.5h, 4h, 4.5h, 5h, etc., or a range consisting of any two of the above values, for example, 3h-4h, 4h-5h, etc. The secondary sintering temperature may be 500°C, 520°C, 540°C, 560°C, 580°C, 600°C, etc., or a range consisting of any two of the above values, for example, 500°C-540°C, 540°C-580°C, 580°C-600°C, etc. The secondary sintering time may be 6 h, 7 h, 8 h, 9 h, 10 h, etc., or a range consisting of any two of the above values, for example, 6 h-8 h, 8 h-10 h, etc.

[0086] In one embodiment, after the step of obtaining the main material, the method may further include: mixing the main material, a carbon source and a fluorine source, and performing a second sintering to obtain a modified lithium manganese iron phosphate composite material.

[0087] After obtaining the main material, it is mixed with a carbon source and a fluorine source and then sintered for a second time to obtain a modified lithium manganese iron phosphate composite material, so that the C element and the F element are coated on the surface of the main material to reduce the dissolution of manganese ions, thereby improving the cycle stability of the positive electrode active material.

[0088] In one embodiment, the second sintering step includes: in a nitrogen environment, pre-sintering a mixture of the main material, the carbon source and the fluorine source at 300°C-450°C for 3h-5h, and then raising the temperature to 500°C-800°C for secondary sintering for 6h-10h.

[0089] After the main material, carbon source and fluorine source are mixed evenly, they are placed in a nitrogen environment and pre-sintered at 300℃-450℃ for 3h-5h, so that the coating layer on the surface of the main material can form a crystal structure and preliminary microscopic morphology. Continuing to perform secondary sintering at 500℃-800℃ for 6h-10h can improve the structure and performance of the coating layer, thereby improving the electrochemical performance of the positive electrode active material.

[0090] Wherein, in the second sintering step, the pre-sintering temperature may be 300°C, 330°C, 380°C, 420°C, 450°C, etc., or a range consisting of any two of the above values, for example, 300°C-380°C, 380°C-450°C, etc. The pre-sintering time may be 3h, 3.5h, 4h, 4.5h, 5h, etc., or a range consisting of any two of the above values, for example, 3h-4h, 4h-5h, etc. The secondary sintering temperature may be 500°C, 560°C, 620°C, 680°C, 740°C, 800°C, etc., or a range consisting of any two of the above values, for example, 500°C-560°C, 560°C-740°C, 740°C-800°C, etc. The secondary sintering time may be 6 h, 7 h, 8 h, 9 h, 10 h, etc., or a range consisting of any two of the above values, for example, 6 h-8 h, 8 h-10 h, etc.

[0091] In one embodiment, the mass ratio of the carbon source and the fluorine source to the host material is (0.1-0.25):1.

[0092] The mass ratio of the carbon source and the fluorine source to the main material is within the above range, so that the coating layer can effectively protect the main material and reduce the dissolution of manganese ions, and can also make the mass ratio of the main material better, thereby making the positive electrode active material have better electrochemical properties.

[0093] The mass ratio of the carbon source and the fluorine source to the main material can be 0.1:1, 0.15:1, 0.2:1, 0.25:1, etc., or a range consisting of any two of the above values, for example, (0.1:1)-(0.2:1), (0.2:1)-(0.25:1), etc.

[0094] In one embodiment, the mass ratio of the carbon source to the fluorine source is 1:(3-9).

[0095] The mass ratio of the C element to the F element in the coating layer is within the above range, which can effectively improve the cycle stability of the positive electrode active material.

[0096] The mass ratio of the C element to the F element in the coating layer may be 1:3, 1:5, 1:7, 1:9, etc., or a range consisting of any two of the above values, for example, (1:3)-(1:5), (1:5)-(1:9), etc.

[0097] In one embodiment, the carbon source includes at least one of glucose and sucrose.

[0098] During the second sintering process, adding at least one of glucose and sucrose and sintering together with the main material can effectively coat the C element on the surface of the main material, thereby improving the stability of the positive electrode active material.

[0099] In one embodiment, the fluorine source includes at least one of ammonium fluoride, lithium fluoride, and iron fluoride.

[0100] During the second sintering process, adding at least one of ammonium fluoride, lithium fluoride, and iron fluoride and sintering together with the main material can effectively coat the F element on the surface of the main material. The F element can form a covalent bond with the C element and the Mn element to improve the structural stability of the main material and the coating layer, thereby improving the cycle stability of the positive electrode active material.

[0101] The third aspect of the present application provides a lithium-ion battery, including the positive electrode active material of the first aspect or / and the preparation method of the positive electrode active material of the second aspect. The lithium-ion battery in the embodiment of the present application has at least the same advantages as the positive electrode active material of the first aspect, or / and the same advantages as the lithium-ion battery prepared by the preparation method of the positive electrode active material of at least the second aspect.

[0102] A fourth aspect of the present application provides an electrical device, comprising the lithium-ion battery of the third aspect. The electrical device in the embodiment of the present application at least has the same advantages as the lithium-ion battery of the third aspect.

[0103] The lithium-ion battery disclosed in the embodiments of the present application can be used in electrical equipment using lithium-ion batteries as power sources or various energy storage systems using batteries as energy storage elements. Electrical equipment can be, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Among them, electric toys can include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles, and spacecrafts, etc.

[0104] In order to make the technical problems, technical solutions and beneficial effects solved by the embodiments of the present application clearer, the following will be further described in detail with reference to the embodiments and the accompanying drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0105] Example 1

Preparation of positive electrode active materials

[0106] (2) Preparation method of lithium iron manganese phosphate material: according to the molar ratio of manganese to iron atoms of 7:3, weigh 0.035 mol manganese sulfate and 0.015 mol ferrous sulfate and dissolve them in 45 mL deionized water, then add 5 mL phosphoric acid (concentration 85 wt%), and then slowly drip 12 mL lithium hydroxide aqueous solution (4 mol / L) into the mixture under vigorous stirring, control the pH of the solution at 4.8-7.0, stir well for half an hour, add 10 mL ethylene glycol and quickly transfer to a high-pressure reactor for hydrothermal reaction, the reaction temperature is 180 ° C and the time lasts for two hours. After cooling to room temperature, wash with ethanol several times, dry in a vacuum drying oven at 80 ° C to constant weight to obtain lithium iron manganese phosphate material (LiMn 0.7 Fe 0.3 PO4).

[0107] (3) Preparation method of main material: The lithium iron phosphate material (LiFePO4) and lithium iron manganese phosphate material (LiMn 0.7 Fe 0.3 PO4) in a molar ratio of 1:6, the temperature was raised to 400°C and kept for 4 hours under nitrogen environment protection, and then raised to 600°C and kept for 8 hours to obtain the main material (LiMn 0.6 Fe 0.4 PO4). The positive electrode active material includes a modified lithium manganese iron phosphate composite material, and the modified lithium manganese iron phosphate composite material includes a main material.

[0108] (4) Preparation method of the main material coated with the coating layer: The main material obtained in step (3) is uniformly mixed with sucrose and amine fluoride at a mass ratio of 1:0.02:0.18, dispersed in ethanol with a solid content of 50%, and ball milled in a ball mill at 400 rpm for 4 hours. Then, the obtained mixed material is heated to 450°C at 5°C / min under nitrogen protection for 3 hours, then heated to 700°C at 5°C / min for 8 hours, and then cooled naturally to obtain the main material coated with the coating layer (LiMn 0.6 Fe 0.4 PO4@FC).

[0109] The positive electrode active material includes a modified lithium iron manganese phosphate composite material, and the modified lithium iron manganese phosphate composite material includes a main material or a main material coated with a coating layer. In embodiment 1, the modified lithium iron manganese phosphate composite material is a main material coated with a coating layer.

[0110]

Preparation of positive electrode

[0111]

Preparation of negative electrode sheet

[0112]

Preparation of electrolyte

[0113]

Diaphragm

[0114]

Battery preparation

[0115] Example 2 The difference from Example 1 is that in the preparation of the positive electrode active material, the lithium iron phosphate material (LiFePO4) and the lithium iron manganese phosphate material (LiMn 0.7 Fe0.3 PO4) in a molar ratio of 2:5, and the main material (LiMn 0.5 Fe 0.5 PO4), the rest is the same as in Example 1 and will not be described again.

[0116] Example 3 The difference from Example 1 is that in the preparation of the positive electrode active material, the lithium iron phosphate material (LiFePO4) and the lithium iron manganese phosphate material (LiMn 0.7 Fe 0.3 PO4) in a molar ratio of 3:4, and the main material (LiMn 0.4 Fe 0.6 PO4), the rest is the same as in Example 1 and will not be described again.

[0117] Example 4 The difference from Example 1 is that in the preparation of the positive electrode active material, the main material (LiMn 0.6 Fe 0.4 PO4), sucrose and amine fluoride in a mass ratio of 1:0.05:0.15. Other details are the same as those in Example 1 and will not be described again.

[0118] Example 5 The difference from Example 1 is that in the preparation of the positive electrode active material, the main material (LiMn 0.6 Fe 0.4 PO4), sucrose, and amine fluoride in a mass ratio of 1:0.028:0.171. Other details are the same as those in Example 1 and will not be described again.

[0119] Example 6 The difference from Example 1 is that in the preparation of the positive electrode active material, in step (3), the lithium iron manganese phosphate material and the lithium iron phosphate material are heated to 200°C for 3 hours under nitrogen environment protection, and then heated to 500°C for 6 hours. In step (4), the mass ratio of the main material to sucrose and fluorinated amine is 1:0.01:0.09. The rest is the same as in Example 1 and will not be repeated here.

[0120] Example 7 The difference from Example 1 is that in the preparation of the positive electrode active material, in step (3), the lithium iron manganese phosphate material and the lithium iron phosphate material are heated to 300°C for 5 hours under nitrogen environment protection, and then heated to 550°C for 10 hours. In step (4), the mass ratio of the main material to sucrose and fluorinated amine is 1:0.025:0.225. The rest is the same as in Example 1 and will not be repeated here.

[0121] Example 8 The difference from Example 1 is that in the preparation of the positive electrode active material, in step (4), the main material is heated to 300°C for 4 hours under nitrogen environment protection, and then heated to 500°C for 6 hours. In step (4), the mass ratio of the main material to glucose and lithium fluoride is 1:0.02:0.18. The rest is the same as in Example 1 and will not be repeated here.

[0122] Example 9 The difference from Example 1 is that in the preparation of the positive electrode active material, in step (4), the main material is heated to 400°C for 5 hours under nitrogen environment protection, and then heated to 800°C for 10 hours. In step (4), the mass ratio of the main material to sucrose and ferric fluoride is 1:0.02:0.18. The rest is the same as in Example 1 and will not be repeated here.

[0123] Comparative Example 1 The difference from Example 1 is that in the preparation of the positive electrode active material, the lithium manganese iron phosphate material (LiMn 0.7 Fe 0.3 PO4) is used as the main material for the first sintering and the second sintering of step (3) and step (4). The rest is the same as in Example 1 and will not be described again.

[0124] Comparative Example 2 The difference from Example 1 is that in the preparation of the positive electrode active material, step (3) is not performed, and the lithium iron phosphate material (LiFePO4) and lithium iron manganese phosphate material (LiMn 0.7 Fe 0.3 PO4) in a molar ratio of 1:6, and then the positive electrode active material is prepared according to step (4). The rest is the same as in Example 1 and will not be described again.

[0125] Comparative Example 3 The difference from Example 1 is that in the preparation of the positive electrode active material, the lithium iron phosphate material (LiFePO4) and the lithium iron manganese phosphate material (LiMn 0.7 Fe 0.3 PO4) After step (3), step (4) is not performed. The rest is the same as in Example 1 and will not be described again.

[0126] The relevant parameter testing methods in the above embodiments and comparative examples are as follows: (1) 0.1C discharge capacity: Charge the battery to 4.25V at 0.1C constant current and constant voltage at 25±2℃, with a cut-off current of 0.05C. After leaving it for 10 minutes, discharge it to 2.5V at 0.1C constant current and leave it for 10 minutes. Repeat the charge and discharge three times and use the third discharge capacity as the judgment.

[0127] (2) First coulombic efficiency test: Charge the battery to 4.25V at 0.1C constant current and constant voltage at 25±2℃, with a cut-off current of 0.05C, record the charge capacity C1, leave it for 10 minutes, then discharge it to 2.5V at 0.1C constant current, record the discharge capacity C2, and leave it for 10 minutes. First coulombic efficiency = C2 / C1 × 100%.

[0128] (3) Initial DCR: The battery was discharged at 1C current for 10s at 25±2℃ and 50% SOC to measure the initial DCR of the soft-pack cell.

[0129] (4) 100-cycle capacity retention rate: The battery was charged to 4.25 V at 0.5 C constant current and constant voltage at 25 ± 2 ° C, with a cut-off current of 0.05 C. After standing for 10 min, it was discharged to 2.5 V at 0.5 C constant current. This cycle was repeated for 500 cycles and the capacity retention rate was recorded. The 100th cycle capacity retention rate (%) = (100th cycle discharge specific capacity / first cycle discharge specific capacity) × 100%.

[0130] Table 1 Preparation process parameters of positive electrode active materials of various embodiments and comparative examples

[0131] Table 2 Performance parameters of positive electrode active materials of various embodiments and comparative examples

[0132] In summary, if Figure 1 and Figure 2 As shown, the particle size of the lithium iron phosphate material prepared in the present application is relatively large, and the particle size of the lithium iron manganese phosphate material is smaller than that of the lithium iron phosphate material. Figure 3 As shown in the figure, after the first sintering of the two materials, the lithium manganese iron phosphate material grows in situ on the surface of the lithium iron phosphate, and the lithium manganese iron phosphate material fills the gaps between the particles of the lithium iron phosphate material due to its small particle size, thereby increasing the content of the lithium manganese iron phosphate. Figure 4 As shown in the figure, after the main material is sintered for the first time, it is sintered for the second time with the carbon source and the fluorine source. The surface of the lithium manganese iron phosphate material and the lithium iron phosphate material is relatively rough, indicating that a coating layer is attached to the surface of the main material. Figure 5 and Figure 6As shown, it can be clearly seen through transmission electron microscopy that the active material surface has a coating layer. At the same time, after elemental analysis of the modified lithium manganese iron phosphate composite material, it can be more intuitively seen that the surface of the modified lithium manganese iron phosphate composite material has C elements and F elements. Figure 5 and Figure 6 This indicates that the fluorine-doped carbon layer was successfully coated.

[0133] As shown in Tables 1 and 2, Table 1 shows the process parameters of the positive electrode active materials of each embodiment and comparative example. Table 2 shows the performance parameters of the positive electrode active materials of each embodiment and comparative example. Compared with Comparative Example 1, the process of preparing the positive electrode active materials of Examples 1-9 of the present application includes sintering the lithium iron manganese phosphate material and the lithium iron phosphate material for the first time. The positive electrode active material prepared in Comparative Example 1 is obtained by coating only one material, lithium iron manganese phosphate. In Examples 1-9, the mixed sintering of the lithium iron manganese phosphate material and the lithium iron phosphate material can retain the crystal structure of both, making the final positive electrode active material more stable. And Examples 1-9 are all the first sintering of the lithium iron manganese phosphate material with a smaller particle size and the lithium iron phosphate material with a larger particle size, so that the two materials can be better matched in terms of particle size, so that there are more active materials per unit volume. It can be proved by Table 2 that the electrochemical properties such as gram capacity and cycle stability of the positive electrode active materials prepared in Examples 1-9 are better than those in Comparative Example 1. Compared with Examples 1-9, Comparative Example 2 does not perform the first sintering of the two materials, so the two materials cannot be fused, and the crystal structures of the two materials cannot be taken into account. Therefore, the positive electrode active material prepared in Comparative Example 2 is lower than that of Examples 1-9 in terms of gram capacity, cycle stability and other electrochemical properties. Compared with Examples 1-9, Comparative Example 3 does not perform coating treatment. The positive electrode active material is directly in contact with the electrolyte, and manganese ions will be dissolved in the lithium iron phosphate material and the lithium manganese iron phosphate material during the charge and discharge cycle, which will reduce the electrochemical performance of the lithium ion battery. Therefore, the electrochemical performance of the positive electrode active material prepared in Comparative Example 3 is also lower than that of Examples 1-9.

[0134] In Example 1-3, as the proportion of iron increases, its electrochemical performance gradually decreases. When the molar ratio of lithium manganese iron phosphate material and lithium iron phosphate material is 6:1, so that the ratio of manganese element to iron element after the two materials are fused is 6:4, the electrochemical performance of the positive electrode active material prepared in Example 1 is better. In addition, the lithium manganese iron phosphate material and the lithium iron phosphate material can cooperate with each other in particle size. When the volume average particle size of lithium manganese iron phosphate and lithium iron phosphate is 300nm and 1.2μm respectively, it can not only retain the characteristics of lithium manganese iron phosphate material with a smaller particle size, but also make the lithium manganese iron phosphate material with a smaller particle size cooperate with the lithium iron phosphate material with a larger particle size, reduce the difficulty of slurry processing, and thus make the prepared positive electrode active material have better electrochemical performance. It can be shown from Example 1 and Examples 4-7 that when the ratio of carbon element to fluorine element is 1:9 and the mass ratio of the coating layer to the main material is 0.2:1, the prepared positive electrode active material has better electrochemical performance. Compared with Example 1, Examples 8 and 9 have different parameters for the second sintering, and different carbon sources and fluorine sources are used. The second sintering temperature that is too high or too low, the length of time, and the structure of the coating material will affect the crystal structure of the positive electrode active material. Therefore, the electrochemical properties of the positive electrode active materials prepared in Examples 8 and 9 are lower than those in Example 1.

[0135] The above are only implementation methods of the present application, and are not intended to limit the patent scope of the present application. Any equivalent structure or equivalent process transformation made using the contents of the present application specification and drawings, or directly or indirectly used in other related technical fields, are also included in the patent protection scope of the present application.

Claims

1. A positive electrode active material, characterized in that: The positive electrode active material includes a modified lithium iron manganese phosphate composite material, which includes a main material. The main material includes a lithium iron phosphate material and a lithium iron manganese phosphate material. The volume average particle size of the lithium iron phosphate material is larger than the volume average particle size of the lithium iron manganese phosphate material. The lithium iron manganese phosphate material and the lithium iron phosphate material are partially fused so that the lithium iron manganese phosphate material grows in situ on the surface of the lithium iron phosphate material.

2. The positive electrode active material according to claim 1, characterized in that The volume average particle size of the lithium manganese iron phosphate material is 100nm-500nm.

3. The positive electrode active material according to claim 1, characterized in that The volume average particle size of the lithium iron phosphate material is 0.8 μm-2 μm.

4. The positive electrode active material according to claim 1, characterized in that The molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material is (1-10):

1.

5. The positive electrode active material according to claim 1, characterized in that The modified lithium manganese iron phosphate composite material includes a structural formula of LiMn x Fe 1-x PO4 material, wherein 0.1≤x≤0.

6.

6. The positive electrode active material according to claim 1, characterized in that The modified lithium iron manganese phosphate composite material further includes a coating layer, which is located on the surface of the lithium iron manganese phosphate material and the lithium iron phosphate material, and the coating layer includes C elements and F elements.

7. The positive electrode active material according to claim 6, characterized in that The mass ratio of the coating layer to the modified lithium manganese iron phosphate composite material is (0.01-0.02):

1.

8. The positive electrode active material according to claim 6, characterized in that The coating layer has a thickness of 2nm-15nm.

9. The positive electrode active material according to claim 6, characterized in that The mass ratio of the C element to the F element is 1:(3-9).

10. A method for preparing a positive electrode active material according to any one of claims 1 to 9, characterized in that: include: A lithium iron manganese phosphate material and a lithium iron phosphate material are mixed and subjected to a first sintering to obtain a main material, wherein the volume average particle size of the lithium iron phosphate material is larger than the volume average particle size of the lithium iron manganese phosphate material, the positive electrode active material includes a modified lithium iron manganese phosphate composite material, and the modified lithium iron manganese phosphate composite material includes the main material.

11. The method for preparing a positive electrode active material according to claim 10, characterized in that: The molar ratio of the lithium manganese iron phosphate material to the lithium iron phosphate material is (1-10):

1.

12. The method for preparing a positive electrode active material according to claim 10, characterized in that: The first sintering step includes: in a nitrogen environment, pre-sintering the mixture of the lithium iron manganese phosphate material and the lithium iron phosphate material at 200° C.-400° C. for 3 h-5 h, and then continuing to increase the temperature to 500° C.-600° C. for secondary sintering for 6 h-10 h.

13. The method for preparing a positive electrode active material according to claim 10, characterized in that: After the step of obtaining the main material, the method may further include: The main material, the carbon source and the fluorine source are mixed, and subjected to a second sintering to obtain the modified lithium manganese iron phosphate composite material.

14. The method for preparing a positive electrode active material according to claim 13, characterized in that: The second sintering step includes: in a nitrogen environment, pre-sintering the mixture of the main material, the carbon source and the fluorine source at 300°C-450°C for 3h-5h, and then continuing to increase the temperature to 500°C-800°C for secondary sintering for 6h-10h.

15. The method for preparing a positive electrode active material according to claim 13, characterized in that: The mass ratio of the carbon source and the fluorine source to the main material is (0.1-0.25):

1.

16. The method for preparing a positive electrode active material according to claim 13, characterized in that: The mass ratio of the carbon source to the fluorine source is 1:(3-9).

17. The method for preparing a positive electrode active material according to claim 13, characterized in that: The carbon source includes at least one of glucose and sucrose.

18. The method for preparing a positive electrode active material according to claim 13, characterized in that: The fluorine source includes at least one of ammonium fluoride, lithium fluoride and ferric fluoride.

19. A lithium ion battery, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 9, or / and the method for preparing the positive electrode active material according to any one of claims 10 to 18.

20. An electrical equipment, characterized in that: Comprising the lithium ion battery as claimed in claim 19.

Citation Information

Patent Citations

  • Cathode material and preparation method thereof

    CN108630936A

  • Lithium iron phosphate positive electrode material modified surface structure, and preparation method and application thereof

    CN108878873A

  • Composite material and preparation method thereof

    CN111613786A

  • Lithium iron phosphate composite material and preparation method thereof, and lithium battery and battery power vehicle using composite material

    CN112670475A

  • Positive electrode active material, electrochemical device, and electronic apparatus

    CN114400322A

Cited By

  • Lithium iron phosphate and lithium manganese iron phosphate mixed positive electrode material, battery and preparation method of lithium iron phosphate and lithium manganese iron phosphate mixed positive electrode material

    CN120237208A

  • A positive electrode material, battery and preparation method of a mixture of lithium iron phosphate and lithium iron manganese phosphate

    CN120237208B

  • Positive electrode material and preparation method thereof, positive electrode plate, battery and energy storage device

    CN121617964A